The Future has a Silver Lining : Genealogies of Glamour - Holert, Tom; Munder, Heike; Penman, Ian; Thaemlitz, Terre; Migros Museum für Gegenwartskunst Zürich (Zürich : JRP Ringier, 2004)
Ataman, Kutlug ; Auder, Michel ; Bool, Shannon ; Bowery, Leigh ; Buetti, Daniele ; Bures Miller, George ; Burr, Tom ; Byars, James Lee ; Cardiff, Janet ; Chaimowicz, Marc Camille ; Cosey Fanni Tutti ; Dellsperger, Brice ; Evans, Cerith Wyn ; Flamm, Christian ; Fleury, Sylvie ; Frame, Allen ; General Idea ; Gertsch, Franz ; Göthe, Julian ; Greer, Fergus ; Heys, John Edward ; Horowitz, Jonathan ; Hujar, Peter ; Hunziker, Daniel Robert ; Ivekovic, Sanja ; Leckey, Mark ; Lüthi, Urs ; Manon ; Martin, Bernhard ; Meckseper, Josephine ; Oppenheim, Meret ; Pazos, Carlos ; Rock, Mick ; Scavullo, Francesca ; Sieverding, Katharina ; Vezzoli, Francesco ; Vallance, Jeffrey ; Wermers, Nicole ; Wilcox, T.J. ; Wols
biog. auteurs p. 248
biog., ind. tent., gr. tent. p. 234-248
Duits
Engels
The Future Has a Silver Lining : Genealogies of Glamour. Migros Museum für Gegenwartskunst Zürich. 2004-08-28. 2004-10-31
boek